Is anastomotic urethroplasty is really superior than BMG augmented dorsal onlay urethroplasty in terms of outcomes and patient satisfaction: Our 4-year experience - Choudhary, Anil Kumar; Jha, Nawal K. (Canadian Urological Association Journal, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Introduction: We analyzed the outcomes of augmented buccal mucosa graft (BMG) dorsal onlay urethroplasty and anastomotic urethroplasty in the management of urethral stricture. Methods: Patients having a stricture length more than 2 cm were treated by augmented BMG dorsal onlay urethroplasty; patients with a stricture length less than 2 cm were managed by excision and end-to-end anastomotic urethroplasty. The postoperative retrograde urethrogram, micturating cystourethrogram, and uroflowmetry were compared to preoperative values. The postoperative subjective symptoms and complications were recorded and analyzed. Results: In total, 90 patients were included in this study. Forty-five patients had an average stricture length of 5.9 cm; they underwent BMG augmented dorsal onlay urethroplasty. Of these, 7 (15.55%) patients came with recurrence, while 38 (84.44%) were asymptomatic, in the average follow-up period of 32.8 months. The next 45 patients underwent excision of the stricture and end-to-end anastomosis. Of these, 6 (13.33%) failed on therapy and the remaining 39 (86.66%) were asymptomatic during the average follow-up period of 28.4 months. Conclusion: The technique of BMG dorsal onlay is easy to do, it is very reliable, has high success rate, less postoperative complications and better patient satisfaction compared to anastomotic urethroplasty. Our study has its limitations. Recurrent cases of urethroplasty and hypospadias were excluded from this study. Recurrent stricture cases were eliminated to overcome bias. Cases of hypospadias are still best treated by axial or random penile skin flap as BMG augmentation cannot create a long urethral tube. Based on our 4-year experience, we recommend BMG augmented urethroplasty long and short segment stricture of the urethra. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->